The Simulation of Electret Effect in Zn0.7Cd0.3S Layers - Kuliešius, F.; Tamošiūnas, S.; Žindulis, A. (Nonlinear Analysis: Modelling and Control, 2005)
The regularities of the dark discharge in ionic contact mode as well as of the thermoelectret effect have been investigated for Zn0.7Cd0.3S layers. The peculiarities of electret charge formation as well as the electret voltage dependences on poling electric field, polarisation time and temperature have been analysed in Zn0.7Cd0.3S layers during the present work. The model of space charge accumulation have been proposed.